Organisational Commitment in the Public Service of Ghana: An Empirical Study. - Abdul-Nasiru, I.; Mensah, R.; Amponsah-Tawiah, K.; Simpeh, K.N.; Kumasey, A.S. (International Knowledge Sharing Platform, 2014)
Overall performance of an organisation depends on several factors including organisational commitment. This phenomenon is a valuable factor that affects policy direction of organisations of today. The current study examines commitment of workers in the civil/public service of Ghana. In the process, the researchers also investigated differences in commitment in terms of age and length of service. Subjects were 343 male and female civil/public servants, drawn from various ministries, departments and agencies. Analyses show that males are more committed than their female counterparts. It was further revealed that age is positively associated with employee commitment, and that longer serving employees are more committed than staff with short tenure in an organisation. The implications were discussed and recommendations made.
Journal Article
Keywords: Civil Service; Ghana; Organisational Behaviour; Organisational Commitment; Public Service